2018
DOI: 10.35808/ersj/1003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Marketing Techniques in the Republic of Kazakhstan and Ukraine

Abstract: Marketing is the driving force of any business, and its implementation in the management process is necessary for the successful functioning of the company. Kazakhstan and Ukraine are countries where the flour-grinding industry holds one of the main positions in the production sector. The current situation in both countries requires a new approach and a rethinking of positions regarding the conduct of business in the flour-grinding industry. This article aims to characterize the current situation in the flour-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Corporate sales involve high risk, multiple stakeholders, lengthy sales cycles, substantial investments, and complex relationships. By contrast, transactional sales carry low risk, involve a limited number of stakeholders, have shorter sales cycles, and focus primarily on marketing and sales activities (Duisebayeva, 2018). Studies have shown that artificial intelligence is currently in demand in corporate sales within the new format of retail business.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate sales involve high risk, multiple stakeholders, lengthy sales cycles, substantial investments, and complex relationships. By contrast, transactional sales carry low risk, involve a limited number of stakeholders, have shorter sales cycles, and focus primarily on marketing and sales activities (Duisebayeva, 2018). Studies have shown that artificial intelligence is currently in demand in corporate sales within the new format of retail business.…”
Section: Literature Reviewmentioning
confidence: 99%